Optimasi Pakan Bibit Unggul Sapi Jantan Menggunakan Particle Swarm Optimization (PSO) (Studi Kasus pada Balai Besar Inseminasi Buatan Singosari) - Daniel Agara Siregar; Imam Cholissodin; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Cows are one of the staple food items needed to meet consumption needs in Indonesia. To produce a quality cow required good quality seed of cow. Based on data from Artificial Insemination Center (BBIB) Singosari, fluctuation in the value of the amount of frozen semen production due to decrease in the number of cow population and reduced production of fresh cement with good quality. Cattle feed is one of the factors that affect the quality of cement in cow. Provision of feed with good nutritional content and the right composition can improve the quality of cow. The Particle Swarm Optimization algorithm is chosen for optimization as it is easy to implement and faster in finding the optimum solution compared to other optimization methods. This problem uses initialization of particles, initial velovity, velocity updates, position updates, finding the fitness value of personal best ​​and global best. After conducting the experiment using the weight of the cow of 1114 kg, in obtaining the most optimal parameter result that is on the swarm size of 180, the number of iterations of 45, the inertia weight of of 0,4 and of 0,5, and the acceleration coefficient and respectively 2,5 and 0,5 and the values ​​of and respectively 0,5 and 2,5. Feed recommendation result by system can retrench fund as much as 32,104% compared to recommendation of feed at BBIB.